Reverse analysis of constitutive properties of sintered silver particles from nanoindentations. (15th May 2020) - Long, X.; Jia, Q.P.; Li, Z.; Wen, S.X.
Abstract: Nanoindentation technology is an effective and convenient method for evaluating the mechanical properties of materials at micro and nano scales. Since the complete nanoindentation process is a typical non-linear mechanical behavior and the material deformation varies with the indentation depth, it is difficult to analytically obtain plastic parameters of constitutive models which are however important to describe the material properties in finite element simulations. In this study, nanoindentation experiments are carried out on the sintered silver nanoparticle (AgNP) which is one of the advanced die-attach materials for high-power electronic devices working in harsh environment. In order to further stabilize and enhance the thermal conductivity, different weight contents of SiC microparticles are incorporated in the AgNP paste before the sintering process. Finite element simulations are used to simulate the deformation and load resistance of materials in nanoindentation process. Plastic properties of materials are analyzed by proposing a reverse algorithm based on the measurements of nanoindentation responses. Essentially, the proposed reverse algorithm couples the dimensional analysis and trial-and-error fitting technique. The complete constitutive relationship of sintered AgNP with different SiC contents is obtained accordingly after examining the loading and unloading stages of nanoindentation responses. The influence of SiC content on the mechanical properties of sintered AgNP is also discussed by considering the material microstructure observed using a scanning electron microscopy. Finally, the uniqueness of constitutive curve from the proposed reverse algorithm is confirmed by the agreement of predicted and measured load-displacement responses using independent spherical indentations.